Renal Artery Stenting Associated With Improvement in Renal Function and Blood Pressure Control in Long-Term Follow-Up - Krzysztof Milewski; Wojciech Fil; Piotr Buszman; Małgorzata Janik; Wojciech Wanha; Todd Martin; Marek Król; Bogdan Gorycki; Szymon Wiernek; Lukasz Krzych; R. Stefan Kiesz; Wojciech Wojakowski; et al. (Karger Publishers, 2016)
Background/Aims: Clinical benefits of percutaneous treatment of renal artery stenosis (RAS) remain controversial. The aim of this study was to evaluate the effects of renal artery stenting on kidney function and blood pressure (BP) control in the log-term follow-up. Additionally angiographic follow up was performed in selected subgroup of patients. Methods: The study was designed as international registry of 265 consecutive patients with RAS treated with renal artery stenting. The primary end-point of the study was the change in renal function and blood pressure at long-term follow-up as compared with baseline values. Evaluation of the renal function was based on estimated glomerular filtration rate (eGFR) with the use of the modification of diet in renal disease (MDRD) formula. Results: All patients had clinical follow-up at the median time of 23.8 (interquartile range: 3-90) months during ambulatory visits. At follow-up eGFR improved in 53,9% of patients. These patients had lower pre-procedural systolic BP, more severe lesion type at baseline and lower diameter stenosis in control angiography. At follow up visits, SBP improvement was observed in 77,4% of patients. The average number of anti-hypertensive medications before the procedure and at follow up did not change significantly (2,70±1,0 vs 2,49±0,9, p=0,1). Restenosis rate based on control angiography performed at median time of 15 months was 12%. Conclusion: The results of the study suggest that interventional treatment of RAS may preserve renal function and improve blood pressure control at long-term follow-up.